Production Regulation Principles and Tax Reforms - Laurence Jacquet; Etienne Lehmann (CESifo GmbH, 2025)
We propose a new approach to assess the impact of regulatory changes on the production sector such as competition policies, taxing intermediate goods, robots or AI, trade regulation, production of public firms or environmental standards for firms. Our framework covers multidimensional nonlinear taxation with multiple income sources, General Equilibrium (GE) adjustments and market failures. We clarify under which conditions on the tax system the production sector should be regulated only to increase aggregate output, a recommendation we label the Production Regulation principle. Under these conditions, regulatory changes can be combined with adequate GE-neutralizing tax reforms to offset the GE effects on taxpayers' utility levels. This ensures that changes in the production sector's regulation that increases aggregate output do not deteriorate individual welfare, thereby resulting in a Pareto improvement. We also provide formulas that balance the effects of regulatory changes on aggregate production and their pre-distributive impact, when a GE-neutralizing tax reform is not feasible. These formulas introduce new GE-multipliers, which also appear in our calculations for the impact of tax reforms, optimal income tax systems and identifying Pareto-improving tax reforms.
Keywords: H21; H22; H23; H24; L50; F13; 330; production efficiency; market frictions; nonlinear income taxation; several income sources; endogenous prices